Islanding detection technique based on vector shift / Nurul Nadia Omar - Omar, Nurul Nadia (2013)
Islanding refers to the condition in which a distributed generator (DG) continues to power a location even though electrical power from the electric utility is no longer present. Islanding can be hazardous to the DG, and should be prohibited. Thus, a reliable and fast detection technique is needed to detect islanding and isolate the DG from the main grid. In this paper, islanding detection technique based on Vector shift (VS) method is presented. This method detects islanding when voltage phase is shifted beyond the threshold limit/setting. A new component known as Vector Shift Detector (VSD) was modeled by using PSCAD simulation tools to detect the changes of phase angle at DG's terminal voltage. A simulation studies on a distribution network with mini hydro generation was carried out to evaluate the VSD model. To evaluate the effectiveness of VSD, it has been tested under various case studies which are loss of mains and different types of faults. The result showed that the VSD was able to distinguish disturbances event would lead to islanding.